SUSTAINABLE ARCHITECTURE IMPLEMENTATION OF VERNACULAR MOSQUE IN ACEH, INDONESIA - Bakri, Maysarah (Journal of Islamic Architecture, 2018)
As one of the build environment’s products, the existence of the building has a positive and negative contribution towards the surrounding. Along with the emerging of the environmental problems, the architecture sector offers the implementation of the sustainable architecture concept of each architecture object include the traditional and modern building. The application of this concept is the solution to solve the environment, social and economic problems which keep emerging. The aim of this concept is the improvement of the quality of those three aspects and the life of humanity itself. This research aims to find the implementation of sustainable architecture’s theory on the vernacular mosque in Aceh. Masjid Tuha, Indrapuri, Aceh Besar is the object of the research. The method is descriptive qualitative which describes the result of observation. The observation is based on the research instrument. The result shows that Masjid Tuha, Indrapuri, Aceh Besar applies 20 of 34 sustainable architecture’s indicators. The cultural conservation aspect implements the most numerous signs which mean the existence of the vernacular building itself is one concept of sustainable architecture. However, some other implementations need to be improved to get the best quality of execution.